Numerical Simulation of Fine Particle Solid-Liquid Two-Phase Flow in a Centrifugal Pump - Yanping Wang; Bozhou Chen; Ye Zhou; Jianfeng Ma; Xinglin Zhang; Zuchao Zhu; Xiaojun Li (Shock and Vibration)
To study the effect of fine particle size and volume concentration on the performance of solid-liquid two-phase centrifugal pump, the mixture multiphase flow model, RNG k-ε turbulence model, and SIMPLEC algorithm were used to simulate the two-phase flow of the centrifugal pump. The effects of particle size and volume concentration on internal pressure distribution, solid volume distribution, and external characteristics were analyzed. The results show that under the design discharge conditions, with the increase of particle size and volume concentration, the internal pressure of the flow field will decrease, and the volume fraction of solid phase in the impeller passage will also decrease as a whole. The solid particles gradually migrate from the suction surface to the pressure surface, and the particles in the volute channel are mainly concentrated in the flow channel near the outlet side of the volute. With the increase of particle size and volume concentration, the negative pressure value at the inlet of centrifugal pump increases, the total pressure difference at the inlet and outlet decreases, and the head and efficiency decrease accordingly.